Responsibility of Digital Platforms in the Distribution of Online Slot Gambling Advertisements in Indonesia - Kurniawan, Adi; Wirya Darma, I Made (Faculty of Law, Universitas Pekalongan, 2024)
The main purpose of this paper is to analyze in depth the responsibility of digital platforms in the distribution of online slot gambling advertisements in Indonesia. The focus of the discussion is directed at the role of social media, especially digital platforms such as Facebook, in distributing online slot gambling advertisements and the form of legal responsibility of digital platforms for the distribution of illegal content, especially online slot gambling advertisements, in Indonesia. This study uses a normative legal research method, which is based on an analysis of applicable written legal norms. The approach used is a conceptual and legislative approach, by examining the provisions in relevant laws and regulations. The results of this study indicate that social media, especially Facebook, have a significant role in distributing online slot gambling advertisements in Indonesia. With millions of users and algorithms that encourage viral content, gambling advertisements can be widely distributed through links, groups, or hidden advertisements. The distribution of this content violates the law, such as Article 303 of the Criminal Code and Article 27 paragraph (2) of the ITE Law. Digital platforms have a legal responsibility to monitor and take action against illegal content. Failure to moderate can be subject to criminal or administrative sanctions based on the principle of strict liability and the regulations of Electronic System Organizers (PSE).